Clinical Features and Analysis of Survival in a Sample of Patients Infected with SARS-COV-2 in the Specialized Hospital for Geriatric and Palliative Medicine “November 13” – Skopje - Veterovska Miljkovic, Lidija; Ljatif-Petrusovska, Salija; Jordanovski, Lazo; Ivanovska, Marika; Bundaleska, Olivera; Brezovska, Elena; Zdraveska, Natasa; Velkova, Emilija (Scientific Foundation SPIROSKI, 2022)
BACKGROUND: New worldwide intensive studies of a new virus called severe acute respiratory syndrome coronavirus-2 (SARS-COV-2) have shown that in its clinical manifestations, the virus has an extremely different expression in different population groups, with age being found to be one of the most common and significant variables. AIM: The objective of this study is to categorize the difference between clinical and laboratory parameters of a sample of patients infected with SARS-COV-2 in the Specialized Hospital for Geriatric and Palliative Medicine “November 13” – Skopje, between survived and deceased patients, impact on the number and severity of comorbidities on the severity of the clinical picture and the survival rate. MATERIALS AND METHODS: In our study, we analyzed data from a sample of 113 patients hospitalized in our institution. The study is cross-sectional and observational, and in the methodology, we analyzed demographic data by gender and age groups, analysis of comorbidities, functional and nutritional status of patients, and risk factors for mortality and survival rate. For this purpose, we used several geriatric scores: Cumulative Illness Rating Scale scale–Geriatric (CIRS-G), degree of functional ability (Bartel), and the Geriatric Nutritional Index (GNRI) score. RESULTS: The deceased patients had a significantly higher CIRS-G score, while no significant difference in functional (Bartel) and GNRI scores was found. Multivariate regression analysis showed that lymphocytopenia and low saturation were high-risk factors for death in the geriatric population. CONCLUSION: Providing hospital-level care for the elderly with SARS-COV-2 contributes to a lower mortality rate.